2023
DOI: 10.1186/s12863-023-01107-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening germplasm and detecting QTLs for mesocotyl elongation trait in rice (Oryza sativa L.) by association mapping

Abstract: Background Rice is one of the most important food crops in the world and mainly cultivated in paddy field by transplanting seedlings. However, increasing water scarcity due to climate change, labor cost for transplanting, and competition from urbanization is making this traditional method of rice production unsustainable in the long term. In the present study, we mined favorable alleles for mesocotyl elongation length (MEL) by combining the phenotypic data of 543 rice accessions with genotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In contrast to previous reports, qMEL2 is a novel QTL associated with the control mesocotyl elongation in rice. The physical position of qMEL2 indicates no overlapping region with previously reported mesocotyl-related QTLs in rice ( Redona et al, 1996 ; Cai et al, 2002 ; Lee et al, 2012 ; Edzesi et al, 2023 ). The qMEL2 , a major mesocotyl QTL explaining nearly 37.5% of the observed phenotypic variance, harbors a set of genes proposed to have diverse molecular functions or be involved in biological processes such as transcription factor activity ( Os02g26430 , encoding a WRKY42 transcription factor, TF), growth and development ( Os02g26490 , no apical meristem (NAM) domain-containing protein, zinc-ribbon domain-containing protein ( Os02g26560 ), a Ubiquitin carboxyl-terminal hydrolase ( Os02g26550 ), a Serine carboxypeptidase homologue ( OsSCP7 , Os02g26480 ), and a gene encoding the Wiskott-Aldrich syndrome protein (WAS, Os02g26370 : a conserved domain analysis revealed that this gene has no functional conserved domain.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast to previous reports, qMEL2 is a novel QTL associated with the control mesocotyl elongation in rice. The physical position of qMEL2 indicates no overlapping region with previously reported mesocotyl-related QTLs in rice ( Redona et al, 1996 ; Cai et al, 2002 ; Lee et al, 2012 ; Edzesi et al, 2023 ). The qMEL2 , a major mesocotyl QTL explaining nearly 37.5% of the observed phenotypic variance, harbors a set of genes proposed to have diverse molecular functions or be involved in biological processes such as transcription factor activity ( Os02g26430 , encoding a WRKY42 transcription factor, TF), growth and development ( Os02g26490 , no apical meristem (NAM) domain-containing protein, zinc-ribbon domain-containing protein ( Os02g26560 ), a Ubiquitin carboxyl-terminal hydrolase ( Os02g26550 ), a Serine carboxypeptidase homologue ( OsSCP7 , Os02g26480 ), and a gene encoding the Wiskott-Aldrich syndrome protein (WAS, Os02g26370 : a conserved domain analysis revealed that this gene has no functional conserved domain.…”
Section: Discussionmentioning
confidence: 58%
“…Mesocotyl elongation and seedling emergence are determinant factors conditioning the number of individuals present in the field. Since the advent of genome sequencing technologies, several techniques have been used to identify QTLs for mesocotyl elongation in rice, including QTL-sequencing (QTL-seq), GWAS ( Lu et al, 2016 ; Wang et al, 2021 ) or linkage or association mapping ( Edzesi et al, 2023 ; Feng et al, 2023 ), and employing diverse mapping populations/germplasm and various DNA marker systems ( Huang et al, 2022 ; Edzesi et al, 2023 ). Previous studies reported QTLs associated with mesocotyl elongation ( qMEL ) on almost all chromosomes of rice 1–5, 7, 9, 11, 12 ( Lee et al, 2012 ; Lu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sowing under a certain depth of soil can protect seeds from adverse environmental conditions, improve nutrient‐use efficiency, and enhance lodging resistance (Sandhu et al, 2019; Wang et al, 2019). However, seedlings must be able to emerge from this soil and, unfortunately, most modern rice cultivars have poor emergence vigor following direct seeding, leading to higher seed usage and resource costs (Edzesi et al, 2023). Previous studies showed that the mesocotyl, a structure between the basal part of the seminal root and the coleoptile node of seedlings, provides vigor when pushing the shoot tip through the soil surface and is essential for the uniform emergence of direct‐seeded rice (Lee et al, 2017; Zhan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%